Every atom counts: elucidating the fundamental impact of structural change in conjugated polymers for organic photovoltaics - Lo, Chi Kin; Gautam, Bhoj R.; Selter, Philipp; Zheng, Zilong; Oosterhout, Stefan D.; Constantinou, Iordania; Knitsch, Robert; Wolfe, Rylan M. W.; Yi, Xueping; Brédas, Jean-Luc; So, Franky; Toney, Michael F.; et al. (Chemistry of materials, 2018)
As many conjugated polymer-based organic photovoltaic (OPV) materials provide substantial solar power conversion efficiencies (as high as 13%), it is important to develop a deeper understanding of how the primary repeat unit structures impact device performance. In this work, we have varied the group 14 atom (C, Si, Ge) at the center of a bithiophene fused ring to elucidate the impact of a minimal repeat unit structure change on the optical, transport, and morphological properties, which ultimately control device performance. Careful polymerization and polymer purification produced three “one-atom change” donor-acceptor conjugated alternating copolymers with similar molecular weights and dispersities. DFT calculation, absorption spectroscopy, and high-temperature solution 1H nuclear magnetic resonance (NMR) results indicate that poly(dithienosilole-alt-thienopyrrolodione), P(DTS-TPD), and poly(dithienogermole-alt-thienopyrrolodione), P(DTG-TPD) exhibit different rotational conformations when compared to poly(cyclopentadithiophene-alt-thienopyrrolodione), P(DTC-TPD). Solid-state 1H MAS NMR experiments reveal that the greater probability of the anticonformation in P(DTS-TPD) and P(DTG-TPD) prevail in the solid phase. The conformational variation seen in solution and solid-state NMR in turn affects the polymer stacking and intermolecular interaction. Two-dimension 1H-1H DQ-SQ NMR correlation spectra shows aromatic-aromatic correlations for P(DTS-TPD) and P(DTG-TPD), which on the other hand is absent for P(DTC-TPD). In a thin-film interchain packing study using grazing incidence wide-angle X-ray scattering (GIWAXS), we observe the π-face of the conjugated backbones of P(DTC-TPD) aligned edge-on to the substrate, whereas in contrast the π-faces of P(DTS-TPD) and P(DTG-TPD) align parallel to the surface. These differences in polymer conformations and backbone orientations lead to variations in the OPV performance of blends with the fullerene PC71BM, with the device containing P(DTC-TPD):PCBM having a lower fill factor and a lower power conversion efficiency. Ultrafast transient absorption spectroscopy shows the P(DTC-TPD):PCBM blend to have a more pronounced triplet formation from bimolecular recombination of initially separated charges. With a combination of sub-bandgap external quantum efficiency measurements and DFT calculations, we present evidence that the greater charge recombination loss is the result of a lower lying triplet energy level for P(DTC-TPD), leading to a higher rate of recombination and lower OPV device performance. Importantly, this study ties ultimate photovoltaic performance to morphological features in the active films that are induced from the processing solution and are a result of minimal one-atom differences in polymer repeat unit structure.